A unique chromosomal in-frame deletion identified among seven XP-C patients - Schubert, Steffen; Gratchev, Alexei (Photodermatology, photoimmunology & photomedicine, 2016)
Background The nucleotide excision repair (NER) pathway, defective in xeroderma pigmentosum (XP) patients, removes DNA photolesions in order to prevent carcinogenesis. Complementation group C (XP-C) is the most frequent group of XP patients worldwide. Methods We analyzed seven XP-C patients clinically and molecular-genetically applying: post-UV cell survival (MTT-assay), quantitative Real-time PCR, sequencing on chromosomal as well as cDNA level, and in silico interpretation of sequencing data. Results All cases displayed diminished post-UV cell survival as well as reduced XPC mRNA levels. Five homozygous and two heterozygous disease causing mutations were identified. A large chromosomal deletion of ~5.8 kb identified in XP174MA leads to an unique in frame deletion of XPC exon 2 and exon 3. In silico analysis revealed the deletion of 102 amino acids in the N-terminal part of XPC while leaving the C-terminal domain intact. The novel c.361delA mutation in XP168MA leads to a frameshift in exon 3 resulting in a premature stop codon 27 codons downstream of the deleted adenine. Conclusion Our analysis confirms that XP-C patients without increased sun sensitivity develop non-melanoma skin cancers earlier than sun-sensitive XP-C patients. Reduced cellular mRNA levels are characteristic for XP complementation group C and qRT-PCR represents a rapid diagnostic tool.